Pembentukan Kesadaran Neurodiversitas dalam Pendidikan Inklusi Berbasis Alam melalui Tinjauan Interaksionisme Simbolik di Sekolah Alam Bandung - Puteri, Salma Aisyah; Sekarningrum, Bintarsih; Lesmana, Aditya Candra (Jayapangus Press, 2025)
This study examines the implementation of inclusive education at Sekolah Alam Bandung in the practice of communication and interpretation of meaning that shapes an adaptive learning environment for neurodivergent students. The theory used in this analysis is symbolic interactionism, which is used to understand the development of awareness and acceptance of student neurodiversity in an inclusive education model. This study employs a qualitative method with a case study approach, with data collected through in-depth interviews, non-participatory observation, and literature review involving 12 informants comprising teachers, staff, parents, and neurodivergent students. The research data was then analyzed using Miles and Huberman's interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that consistent symbolic interaction, positive interpretations of neurodivergent behavior, and the collective use of inclusive language collectively reconstruct the social reality of neurodiversity from a deficit to a valued natural variation. This study concludes that the success of inclusion at Sekolah Alam Bandung is rooted in the community's ability to create and maintain shared meanings that support diversity, offering important implications for the development of broader inclusive education models and efforts to address stigma and promote more inclusive policies.